DESIGN OF REAR WHEEL DISC BRAKES YAMAHA R25 250 CC MOTORCYCLE 2015 - Aceng, Aceng Hilman Muhammad Mazid; Santosa, Aa; Oleh, Oleh (Jurnal Mekanika dan Manufaktur, 2022)
Motorcycle is one of the two-wheeled vehicles that are often used and we encounter in everyday life. Motorcycles consist of various components and parts that have their respective functions. The engine elements of a motorcycle are designed in such a way as to suit the desired function. Brake is a component or device used to slow down or stop the vehicle through friction. The design of brake components is carried out in order to obtain a design result that is in accordance with the function of the brake component which will later become a recommendation. Several factors in brake design are braking force, torque, braking power, wear volume, life time and materials. From the calculation results obtained the value of braking force (Pv) of 87.5 kg, torque (MR) of 3128 kg.cm, volume of wear 6.75 cm³, service life of 140 hours and with Asbestos Passed Hidraulically and AISI 1045 materials.